The collected works (gsuṅ ʼbum) of Thaṅ-stoṅ-rgyal-po - Thaṅ-stoṅ-rgyal-po, 15th cent (Kunsang Topgey, 1976)
Writings, largely on Buddhist meditation and ritual, of a master of the Shangpa Kargyudpa tradition.